A percutaneous fetal cardiac catheterization technique for pulmonary valvuloplasty and valvulotomy in a mid‐gestation lamb model. (24th September 2014) - Edwards, Andrew; Veldman, Alex; Nitsos, Ilias; Chan, Yuen; Brew, Nadine; Teoh, Mark; Menahem, Samuel; Schranz, Dietmar; Wong, Flora Y.
Abstract Objective We aimed to assess the feasibility of using a percutaneous transhepatic cardiac catheterization technique to perform fetal pulmonary valvuloplasty and valvulotomy under ultrasound guidance at mid‐gestation. Method In 13 mid‐gestation fetal lambs without cardiac pathology, percutaneous transhepatic cardiac catheterization was used to position a coronary angioplasty catheter within the pulmonary valve. The balloon was inflated/deflated several times, simulating pulmonary valvuloplasty. In another two fetal lambs, a guidewire tip was positioned against the pulmonary valve, and unipolar diathermy was applied to simulate perforation of an atretic valve. Results Percutaneous access followed by right heart catheterization was successful in all cases. One fetus died following right ventricle perforation. Simulated pulmonary valvuloplasty was successful in nine cases using catheters with 6‐mm‐long balloons but unsuccessful in two cases (both survived) using 12‐mm‐long balloons. In one case, the catheter could not be inserted as the cannula became dislodged. Diathermy of the pulmonary valve was successful in both attempts. Conclusion We successfully simulated in utero perforation and dilation of the pulmonary valve using percutaneous transhepatic access in fetal lambs. The technique has potential for clinical translation into treatment for human fetuses with critical pulmonary stenosis or pulmonary atresia with intact ventricular septum. © 2014 John Wiley & Sons, Ltd.